Political Mobilization in American Congregations: A Religious Economies Perspective - Djupe, Paul A. (Politics and religion, 2019)
It has become an article of faith that congregations in America play an important role in the political mobilization of the faithful, but the reasons why congregations themselves provide political opportunities are not well understood. We unite various strands of work about congregational political engagement under the canopy of the religious economies model. Using the 2001 U.S. Congregational Life Study and 1998 National Congregations Study datasets, we show that market forces shape churches' provision of political goods, suggesting that the congregational embrace of political activities should be understood not as a politically strategic exercise, but as another way to reach out to new members and retain current ones.